(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Oncologic emergencies are complications resulting from cancer itself or from treatment of cancer requiring immediate attention & reversal. It is an acute life threatening event, may be the first sign of disease or may indicate disease progression. Cancer patients presenting with oncologic emergencies should be approached in a similar way to those without cancer. The care of cancer patients with oncologic emergencies is a challenge not only to oncologists but also to clinicians involved in emergency medicine. It requires rapid intervention to avoid death or severe permanent damage. The overall goal is to prevent, reverse or minimize life threatening complications through prophylaxis, early detection and specific management. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20982 J Bangladesh Coll Phys Surg 2013; 31: 150-155